Current developments and opportunities of pluripotent stem cells-based therapies for salivary gland hypofunction - Song, Wenpeng; Liu, Huan; Su, Yingying; Zhao, Qian; Wang, Xiaoyan; Cheng, Pengfei; Wang, Hao (Frontiers in Cell and Developmental Biology, 2024)
Salivary gland hypofunction (SGH) caused by systemic disease, drugs, aging, and radiotherapy for head and neck cancer can cause dry mouth, which increases the risk of disorders such as periodontitis, taste disorders, pain and burning sensations in the mouth, dental caries, and dramatically reduces the quality of life of patients. To date, the treatment of SGH is still aimed at relieving patients' clinical symptoms and improving their quality of life, and is not able to repair and regenerate the damaged salivary glands. Pluripotent stem cells (PSCs), including embryonic stem cells (ESCs), induced pluripotent stem cells (iPSCs), and expanded pluripotent stem cells (EPSCs), are an emerging source of cellular therapies that are capable of unlimited proliferation and differentiation into cells of all three germ layers. In recent years, the immunomodulatory and tissue regenerative effects of PSCs, their derived cells, and paracrine products of these cells have received increasing attention and have demonstrated promising therapeutic effects in some preclinical studies targeting SGH. This review outlined the etiologies and available treatments for SGH. The existing efficacy and potential role of PSCs, their derived cells and paracrine products of these cells for SGH are summarized, with a focus on PSC-derived salivary gland stem/progenitor cells (SGS/PCs) and PSC-derived mesenchymal stem cells (MSCs). In this Review, we provide a conceptual outline of our current understanding of PSCs- based therapy and its importance in SGH treatment, which may inform and serve the design of future studies.